The Use of Assisted Reproductive Technology by European Childhood Cancer Survivors - Borgmann-Staudt, Anja; Michael, Simon; Sommerhaeuser, Greta; Fernandez-Gonzalez, Marta-Julia; Friedrich, Lucia Alacan; Klco-Brosius, Stephanie; Kepak, Tomas; Kruseova, Jarmila; Michel, Gisela; Panasiuk, Anna; Schmidt, Sandrin; Lotz, Laura; et al. (Current Oncology, 2022)
CCS often wish to have biological children yet harbour concerns about fertility impairment, pregnancy risks and the general health risks of prospective offspring. To clarify these concerns, health outcomes in survivor offspring born following ART (n = 74, 4.5%) or after spontaneous conception (n = 1585) were assessed in our European offspring study by descriptive and bivariate analysis. Outcomes were compared to a sibling offspring cohort (n = 387) in a 4:1 matched-pair analysis (n = 1681). (i) Survivors were more likely to employ ART than their siblings (4.5% vs. 3.7%, p = 0.501). Successful pregnancies were achieved after a median of one cycle with, most commonly, intracytoplasmic sperm injection (ICSI) using non-cryopreserved oocytes/sperm. (ii) Multiple-sibling births (p < 0.001, 29.7% vs. 2.5%), low birth weight (p < 0.001; OR = 3.035, 95%-CI = 1.615–5.706), and preterm birth (p < 0.001; OR = 2.499, 95%-CI = 1.401–4.459) occurred significantly more often in survivor offspring following ART utilisation than in spontaneously conceived children. ART did not increase the prevalence of childhood cancer, congenital malformations or heart defects. (iii) These outcomes had similar prevalences in the sibling population. In our explorative study, we could not detect an influence on health outcomes when known confounders, such as multiple births, were taken into account.
CRIS-Team Scopus Importer:2022-09-09
Keywords: ART; cancer; childhood and adolescence; health outcome; offspring; survivor